Utilizing Simulink and MATLAB graphical user interface in modelling and simulation of chaos-based digital modulation techniques - Ogras, Hidayet; Turk, Mustafa (Sage Publications Ltd, 2013)
This paper describes a software package which is designed using MATLAB's Graphical User Interface (GUI) in order to provide a tool to be used for chaos-based digital communication systems. The basic working principle of this software package (Chaos-based Digital Communication System Simulation Package, CDCSSP) is to perform simulations of chaos-based digital modulation types under different conditions such as distinct chaotic oscillators and channel noise effects. Power spectra of the signals, some important time domain signals and Bit Error Rate (BER) curves for all the modulation types can be observed graphically by using CDCSSP. The main purpose of CDCSSP is to give preliminary information about chaos-based digital modulation schemes by using a visual interface with the graphical and numerical results of the simulations. T-test statistical analysis demonstrates how successful CDCSSP is in terms of enhancing student learning for educational purposes. CDCSSP can be used for educational purposes as an easy-to-use and user-friendly visual instruction tool.
Keywords: chaos; digital modulation; engineering education; MATLAB-GUI; modelling; Simulink